DEVELOPMENT OF A BIOTECHNOLOGY PRACTICUM MANUAL TO IMPROVE THE SCIENCE PROCESS SKILLS - Nur Asykin; Haslinda Yasti Agustin (EDUCATUM: Scientific Journal of Education, 2024)
Practical activities are one part of the science learning process which requires teaching materials in the form of practical manuals that are specific to the learning material. The research objectives are to describe the development results, validity results, practicality results, and analyze the effectiveness results of the Biotechnology practicum manual to improve students' science process skills. The research method uses R&D and the ADDIE development model. The results of the research are the development of a Biotechnology practicum manual consisting of, front cover, foreword, table of contents, list of pictures, practicum rules, format and rules for writing practicum reports, procedures for using the practicum manual, competencies to be achieved, practicum topics, author profile , and back cover. The results of the product validity value of practical manuals for material experts were 98.4%, media experts were 83.75%, and practitioners were 96.92%. The practicality value of the student response test practicum manual product was 87.61%. The results of the effectiveness value of the practical manual for the experimental class were greater than those for the control class, namely 68.37 > 51.37. The results of the analysis of the Independent sample T-test, the significance value (2-tailed) is 0.000 (<0.05), meaning that there is a significant difference between the control class and the experimental class. The conclusion is that there is an influence of using the Biotechnology practical manual on the science process skills of class IX students in Kalidawir 1 Middle School.